1995
DOI: 10.1021/bi00047a020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of tRNA-Guanine Transglycosylase from Escherichia coli by 2-Amino-5-(fluoromethyl)pyrrolo[2,3-d]pyrimidin-4(3H)-one

Abstract: In Escherichia coli, tRNA-guanine transglycosylase (TGT) catalyzes the incorporation of the queuine precursor preQ1 [2-amino-5-(aminomethyl)pyrrolo[2,3-d]pyrimidin-4(3H)-one] into tRNA. This precursor is further elaborated to queuine by two subsequent enzymic reactions [Slany, R. K., & Kersten, H. (1994) Biochimie 76, 1178-1182]. Our previous studies [Hoops, G. C., Townsend, L. B., & Garcia, G. A., (1995) Biochemistry (in press)] on a series of synthetic 5- and 6-substituted 2-aminopyrrolo[2,3-d]pyrimidin-4(3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Although this rate of washout is low (slow) it does provide evidence that the first chemical step can occur in the absence of the second substrate. Finally, ping-pong kinetics are consistent with our earlier study of a mechanism-based inhibitor of TGT, 7-fluoromethyl-7-deazaguanine (FMPP) [38]. In those studies, we observed that FMPP inactivation of TGT was dependent upon tRNA and that FMPP is competitive with respect to guanine, consistent with FMPP interacting with a covalent TGTtRNA intermediate.…”
Section: Discussionsupporting
confidence: 89%
“…Although this rate of washout is low (slow) it does provide evidence that the first chemical step can occur in the absence of the second substrate. Finally, ping-pong kinetics are consistent with our earlier study of a mechanism-based inhibitor of TGT, 7-fluoromethyl-7-deazaguanine (FMPP) [38]. In those studies, we observed that FMPP inactivation of TGT was dependent upon tRNA and that FMPP is competitive with respect to guanine, consistent with FMPP interacting with a covalent TGTtRNA intermediate.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to a thorough understanding of the kinetics of the TGT reaction, studies over the last decade have helped define the recognition of both the tRNA [22,[25][26][27][28][29][30][31][32][33] and heterocyclic base substrates [34][35][36] and have also helped unveil the roles that certain active-site amino acid residues serve in catalysis. Early work in our laboratory determined that TGT is a zinc metalloenzyme.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%
“…2 Source Organism <1> Escherichia coli [1,4,10,15,16,17,18,19,21,22,23,24] <2> Oryctolagus cuniculus [2,5,20] <3> Salmonella typhimurium [3] <4> Xenopus laevis [6,8] <5> Triticum aestivum [7] <6> Rattus norvegicus [9] <7> Mus musculus [11] <8> Homo sapiens [11,13] <9> Shigella flexneri [11,12,23] <10> Haemophilus influenza [11] <11> Helicobacter pylori [11] <12> Synechocystis sp. [11] <13> Thermotoga maritima [11] <14> Caenorhabditis elegans [11] <15> Methanococcus jannaschii [11] <16> Archaeoglobus fulgidus [11] <17> Methanobacterium thermoautotrophicum [11] <18> Zymomonas mobilis [14,24] <19> Pyrococcus horikoshii [15] 3 Reaction and Specificity…”
Section: Recommended Namementioning
confidence: 99%
“…Substrates and products S 2-amino-5-(fluoromethyl)pyrrolo [2,3-d]pyrimidin-4(3H)-one + tRNAguanine <1> (<1>, 2-amino-5-(fluoromethyl)pyrrolo [2,3-d]pyrimidin-4(3H)one appears to partition between: 1. normal turnover, 2. inactivation, 3. an alternative processing to an unidentrified fluoride-released product [19]) (Reversibility: ? <1> [19]) [19] P guanine + tRNA2-amino-5-(fluoromethyl)pyrrolo [2,3-d]pyrimidin-4(3H)one S 2-thiohypoxanthine + tRNAguanine <6> (Reversibility: ? <6> [9]) [9] P guanine + tRNA2-thiohypoxanthine S 6-thioguanine + tRNAguanine <6> (Reversibility: ?…”
Section: Reaction Type Pentosyl Group Transfermentioning
confidence: 99%
See 1 more Smart Citation